1994
DOI: 10.2307/3283194
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Contracaecum multipapillatum (Nematoda: Anisakinae) from Mexico in the Domestic Cat

Abstract: Juveniles of Contracaecum multipapillatum infected the Mayan cichlid (Cichlasoma urophthalmus) and adults infected the olivaceous cormorant (Phalacrocorax olivaceus) and the great egret (Casmerodius albus) in the coastal lagoon at Celestun, State of Yucatan, Mexico. All are new host records, and, even though the geographic locality record of Mexico for the species has not been published, unidentified but presumably conspecific specimens have been reported from there. When juveniles of C. multipapillatum were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…This parasite can also cause granuloma in dogs that eat fish. Contracaecum multipapillatum is also capable of infecting domestic cats [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…This parasite can also cause granuloma in dogs that eat fish. Contracaecum multipapillatum is also capable of infecting domestic cats [35,37].…”
Section: Discussionmentioning
confidence: 99%
“…Although much less invasive than nematodes of the genera Anisakis and Pseudoterranova, larvae of Contracaecum species have been shown experimentally to be infective to mammals (Vidal-Martinez et al 1994), and have occasionally been identified in people (see Beaver et al 1984). Their preferred occurrence in visceral organs, rather than the flesh of fish, limits their zoonotic potential.…”
Section: Abstract: Nematodes · Inshore Fish · Anisakidae · Contracaecummentioning
confidence: 99%
“…multipapillatum s.l. has been found both in commercially important fish of the mullet family Mugilidae (as L3) and in brown pelicans Pelecanus occidentalis (as L3, L4 and adults) from Mexico and other regions of America (Deardorff & Overstreet 1980, Iglesias et al 1998, 2011, Valles-Ríos et al 2000, Valles-Vega 2011, 2014. Furthermore, in these areas, where mullets form part of the diet of these birds, infections have been found in brown pelicans as young as 2 wk (Humphrey et al 1978).…”
Section: Introductionmentioning
confidence: 99%